Stable isotope ratio analysis: an emerging tool to trace the origin of falsified medicines - Roncone, A; Kelly, SD; Giannioti, Z; Hauk, C; Caillet, C; Newton, PN; Perez-Mon, C; Bontempo, L (Elsevier, 2024)
Falsified medicines pose a serious threat to global public health. Over the past few decades, the number of public health issues and seizures of falsified medicines has dramatically increased across the world. The development of new analytical techniques for the identification and traceability of these products hold great promise for innovation to help curtail the high number of deaths caused by the lack of adequate treatments and in combating the criminals responsible for manufacturing these products. This review presents the main approaches, based on stable isotope ratios of the bio-elements, mainly Isotope Ratio Mass Spectrometry and Site-specific Natural Isotopic Fractionation by Nuclear Magnetic Resonance, that can contribute to identifying the origin of these products, both in terms of geographical origin and raw materials employed as well as for the batch controls by the producers.